Coronary Angiography and Percutaneous coronary Intervention in Anomalous Origin of Right Coronary Artery Arising from the Left Sinus of Valsalva - Poudel, Chandra Mani; Gajurel, Ratna Mani; Shrestha, Hemant; Devkota, Surya; Thapa, Sanjeev; Khanal, Rajaram; Shakya, Smriti; Manandhar, Bhawani; Yadav, Vijay (Nepalese Heart Journal, 2022)
Background and Aims: To assess the difficulties encountered while performing coronary angiography and percutaneous coronary intervention in anomalous right coronary artery arising from the left sinus of Valsalva. Methods: Between January 2016 and December 2020, a total of 23 patients underwent coronary angiography and eight underwent percutaneous coronary intervention for an angiographic significant lesion in the anomalous right coronary artery arising from the left sinus of Valsalva. The vascular approach, usage of catheters, fluoroscopic time, and the amount of contrast used were also assessed. Results: Among 6000 coronary angiography and 1500 percutaneous coronary intervention performed, 33 patients (0.55%) had right coronary artery arising from the left sinus of Valsalva. Altogether, 14 patients had type-A, seven had Type-B, eight had Type-C, and four had Type-D anomalous right coronary artery arising from the left sinus of Valsalva. Coronary Angiography was accomplished with the Tiger catheter in 13 patients, Judkins left JL in 8 patients, and Extra-backup (XB3) in one patient. In the percutaneous coronary intervention group, cannulation was done with Judkins left (JL), Amplatz left (AL), and XB in five, two, and one patient respectively and among five type-A patients, four were cannulated with JL and one with XB; one Type-B with JL4; and two Type-C with AL2. The mean fluoroscopic time and contrast volume consumption for coronary angiography and percutaneous coronary intervention were 9.9 minutes and 47 minutes respectively and 63ml and 229 ml respectively. Conclusion: Coronary intervention of anomalous right coronary artery arising from the left sinus of Valsalva is difficult due to inappropriate selection of guide catheter and is associated with a higher both mean fluoroscopic time and contrast volume. Radial route is equally effective for successful procedure.